Rekontruksi Soal SMP Negeri 13 Semarang Sesuai Standar Asesmen Nasional - Chaerunnissa; Imtiyaza Nihlah Hadana; Deby Luriawati Naryatmojo; Wagiran (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Evaluation of improving the quality of education to measure the achievement of student learning in the field of education is called a national assessment. This national assessment focuses on improving student achievement in the fields of literacy, numeracy, character, active learning processes, and a supportive learning atmosphere. National assessments are mandatory for all schools in Indonesia, including SMP Negeri 13 Semarang. This study was conducted to analyze and reconstruct the contents of the national assessment carried out at SMP Negeri 13 Semarang. This study was compiled with a qualitative research scheme that uses a qualitative descriptive method using three stages, namely data reduction, data presentation, and drawing conclusions. The results obtained from this study indicate that several questions in the fields of literacy and numeracy still need to be reviewed and adjusted to the cognitive level of students. The results of the reconstruction provided in this study are expected to provide new and useful insights in the field of education.